2014
DOI: 10.1016/j.biopsych.2013.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Oxytocin Mediates Social Buffering of the Stress Response

Abstract: Background While stressful life events can enhance the risk of mental disorders, positive social interactions can propagate good mental health and normal behavioral routines. Still, the neural systems that promote these benefits are undetermined. Oxytocin is a hormone involved in social behavior and stress; thus, we focus on the impact that social buffering has on the stress response and the governing effects of oxytocin. Methods Female prairie voles (Microtus ochrogaster) were exposed to 1 hr immobilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
268
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 295 publications
(302 citation statements)
references
References 50 publications
22
268
2
1
Order By: Relevance
“…It is possible that oxytocin reduced anxiety, resulting in an increased propensity to socially engage with the caregiver. Several studies have shown that oxytocin has stress-buffering effects that are manifested behaviorally in terms of reduced anxiety and increased affiliative motivation (42,64) and physiologically in terms of reduced activity of the hypothalamic-pituitary adrenal (HPA) axis (41,65). The present finding of decreased salivary cortisol following oxytocin administration is consistent with these results, as well as reports that oxytocin locally affects several hypothalamic nuclei, e.g., through dendritic release (66).…”
Section: Discussionsupporting
confidence: 91%
“…It is possible that oxytocin reduced anxiety, resulting in an increased propensity to socially engage with the caregiver. Several studies have shown that oxytocin has stress-buffering effects that are manifested behaviorally in terms of reduced anxiety and increased affiliative motivation (42,64) and physiologically in terms of reduced activity of the hypothalamic-pituitary adrenal (HPA) axis (41,65). The present finding of decreased salivary cortisol following oxytocin administration is consistent with these results, as well as reports that oxytocin locally affects several hypothalamic nuclei, e.g., through dendritic release (66).…”
Section: Discussionsupporting
confidence: 91%
“…Most previous rodent studies of stress effects on social behavior have used pair-bonded, monogamous rodents to demonstrate a phenomenon called stress buffering, where pair-bonded opposite-sex mates reduce their response to stress via prosocial, affiliative behaviors such as huddling (Smith and Wang, 2014) (reviewed in (Beery and Kaufer, 2015)). Outside of monogamously bonded adult rodents, developmental studies of human and nonhuman primates have provided evidence for both impaired social functioning and enhanced resilience after exposure to early life stress (Dettmer and Suomi, 2014;Gunnar, 2000;Parker et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Oxytocin release within the paraventricular nucleus of the hypothalamus, triggered by mating, mediated mating-induced anxiolytic behavior in male rats 211 . Oxytocin release that was independent of mating was involved in the buffering of stress-induced increases in anxiety-like behaviors and circulating corticosterone that occur in female prairie voles if the male partner is present 212 . Furthermore, social buffering in rats was also shown to protect from the development of alterations in social interactions that otherwise emerge following stress exposure 213 .…”
Section: Box 5 Social Buffering Of Stress In Rodents: Effects and Mementioning
confidence: 99%